THE EFFECTIVENESS OF VARIOUS TYPES OF INTERACTIVE METHODS IN TEACHING ENGLISH FOR YOUNG LEARNERS - Ikromova Muazzam Dilmurod kizi (Web of Journals Publishing, 2024)
The purpose of this study is to analyse the effectiveness of using interactive technologies in the process of teaching a foreign language at a higher educational institution. The principal result of our research is the analysis of the influence of using interactive techniques on acquiring communicative competence and personal development. The major conclusions estimate the significance of applying interactive technologies in learning process. Moreover, in this article particulars which is considered one of the present-day issues in the English language lessons using interactive methods and its importance.
Keywords: interactive methods, learning process, English, interactive material, technology, education.